2008
DOI: 10.1128/jb.01633-07
|View full text |Cite
|
Sign up to set email alerts
|

Additional In Vitro and In Vivo Evidence for SecA Functioning as Dimers in the Membrane: Dissociation into Monomers Is Not Essential for Protein Translocation in Escherichia coli

Abstract: SecA is an essential component in the Sec-dependent protein translocation pathway and, together with ATP, provides the driving force for the transport of secretory proteins across the cytoplasmic membrane of Escherichia coli. Previous studies established that SecA undergoes monomer-dimer equilibrium in solution. However, the oligomeric state of functional SecA during the protein translocation process is controversial. In this study, we provide additional evidence that SecA functions as a dimer in the membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 33 publications
(51 reference statements)
3
54
0
Order By: Relevance
“…At 100 mM KCl, the SecA (no His) dimer is only approximately 10-fold tighter than that of SecA ⌬2-11 (Table 1). This finding is consistent with previous studies, in which SecA ⌬2-11/N95 was found to exist primarily in the dimeric state in low-ionic-strength buffers (43,44).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…At 100 mM KCl, the SecA (no His) dimer is only approximately 10-fold tighter than that of SecA ⌬2-11 (Table 1). This finding is consistent with previous studies, in which SecA ⌬2-11/N95 was found to exist primarily in the dimeric state in low-ionic-strength buffers (43,44).…”
Section: Resultssupporting
confidence: 83%
“…In addition, SecA F263X and F10X produce a cross-linked dimer band with a faster electrophoretic mobility than other variants. The aberrant SDS-PAGE mobilities may result from changes in conformation dependent on the location of cross-linked residues (34), as observed in previous chemical cross-linking experiments (17,28,44).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, a recent single-molecule study suggested that the dimeric organization of SecA is maintained when actively engaged in preprotein translocation [93]. Covalent stabilization of the SecA dimer by crosslinking did not interfere with the protein translocation activity [93,103,108,109]. In this respect, the T. maritima SecYEG-SecA crystal structure shows a monomer of SecA bound to SecYEG, but this structure may not reflect the physiological oligomeric state of SecA as the crystallization process was accompanied with detergents and high salt, both of which have been shown to negate interactions in a SecA dimer interface [93,106].…”
Section: The Motor Protein Secamentioning
confidence: 99%
“…Both in vivo and in vitro protein cross-linking techniques have been utilized to assess the fraction of the SecA dimer in soluble and membrane-bound states. Unfortunately, the studies have produced equivocal results (17,23,24,32) that are of limited value; on the one hand, cross-linking traps proteins in the oligomeric state and thus distorts a natural equilibrium, while on the other hand, suboptimal cross-linking conditions (e.g., nonideal cross-linker chemistry, insufficient cross-linker concentration, or nonphysiological buffer or salt conditions) can lead to underrepresentation of the true oligomeric population. Genetic techniques have been utilized to engineer SecA dimers that were linked in a head-to-tail fashion, and such modified proteins were found to be functional both in vivo and in vitro (22,32).…”
mentioning
confidence: 99%